2020
DOI: 10.1111/jonm.12954
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the general well‐being of nurses in a tertiary Chinese hospital: A cross‐sectional study

Abstract: Background: Good general well-being of nurses is associated with reduced burnout and improved patient safety. However, few studies explored the factors of nurses' general well-being. Aim:The study aimed to assess general well-being and its predictors among hospital nurses. Methods:The study recruited 573 nurses working in a tertiary Chinese hospital to complete a survey of sociodemographic characteristics, DiSC ® personality profile, Self-Rating Anxiety Scale and general well-being. Multivariate linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…Stress and anxiety are common mental health problems among nurses. The results of this study showed an anxiety score of 49.01± 5.46, which was slightly higher than those reported by Yu [22] and Yang [23]. We found that 32.23% of EFO nurses had perceived stress in the present study, and previous studies also revealed that being a nurse was highly stressful [12,15], especially for nurses working in emergency departments [39].…”
Section: Anxiety Stress and Stress Coping Style Of Efo Nursescontrasting
confidence: 58%
See 1 more Smart Citation
“…Stress and anxiety are common mental health problems among nurses. The results of this study showed an anxiety score of 49.01± 5.46, which was slightly higher than those reported by Yu [22] and Yang [23]. We found that 32.23% of EFO nurses had perceived stress in the present study, and previous studies also revealed that being a nurse was highly stressful [12,15], especially for nurses working in emergency departments [39].…”
Section: Anxiety Stress and Stress Coping Style Of Efo Nursescontrasting
confidence: 58%
“…SAS, compiled by ZUNG [21] in 1971, can better measure the anxiety feelings and severity of the subjects, and is widely used in various professions. In China SAS scale had been used for the nurses [22,23]. SAS has 20 items and uses a 4-point scoring system to measure the frequency of symptoms (1=no or little time, 2=a small part of the time, 3=a considerable amount of time, 4=most or all of the time).…”
Section: Self-rating Anxiety Scale (Sas)mentioning
confidence: 99%
“…Regarding marital status, statistically significant differences were found, in this case, favoring married when compared to single. This is in line with previous studies using either the PWI ( Van Beuningen and De Jonge, 2011 ) or other instruments ( Yu et al, 2020 ). Being married, then, seems to function as a protector of wellbeing, beyond instruments and populations, including the palliative care context.…”
Section: Discussionsupporting
confidence: 93%
“…Research has revealed that a high level of job well-being has a positive impact on nurses' work enthusiasm, efficiency, and job satisfaction, while a low level of job well-being results in problems such as work-related exhaustion and increased conflict with patients [4]. In addition, lack of happiness at work is a major reason why nurses quit their jobs [5]. In Europe, 43 % of nurses consider leaving their job within three years [6].…”
Section: Introductionmentioning
confidence: 99%